The Case of Zadar Proconsul Gregorius’ Ciborium – Spolia as a Template for a New Monument - Kraljević, Lucija (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić's 70th birthday, 2020)
Relying on the already established observation that the rear arcade of Proconsul Gregorius' ciborium from the Zadar Cathedral displays stylistic and morphological features which sharply distinguish it from other three arcades of this immensely important liturgical installation with great historical significance, the authors will try to provide a detailed analysis to support this observed fact. They will present arguments to corroborate the opinion that the rear arcade belonged to an earlier, pre-Romanesque ciborium from the Cathedral, and was used as spolia to construct a new high altar ciborium in the 1030s, determining its size and by and large its overall appearance. While the front and two lateral arcades have already been recognized as the work of the so called Zadar-Solin (Split) Stone Carvers' Workshop, the authors attribute its rear arcade to the stone carving production of the so called Master of Zadar Ambos, which dates it to the first decade of the 9th century. In conclusion, they also reflect on certain technical details involved in the construction of an early Romanesque ciborium as a new form of liturgical installation and propose a hypothesis regarding the potential origin of a Zadar ciborium that bears a strong resemblance to this one.